Protein and mRNA Expression Levels of Interleukin-17A, -17F and -22 in Blood and Skin Samples of Patients with Mycosis Fungoides - Despoina Papathemeli; Aikaterini Patsatsi; Dimitrios Papanastassiou; Triantafyllia Koletsa; Thomas Papathemelis; Chrysostomos Avgeros; Olga Pikou; Elizabeth Lazaridou; Elisavet Georgiou (Medical Journals Sweden, 2020)
This study investigated the expression of interleukin (IL)-17A, -17F and -22 in mycosis fungoides. Blood samples were collected from 50 patients with mycosis fungoides and 50 healthy controls. Skin samples were obtained from 26 patients with mycosis fungoides and 5 healthy controls. Protein levels of IL-17A, -17F and -22 were measured in serum by multiplex enzyme-linked immunosorbent assay, and mRNA expression levels were measured in blood and skin samples by real-time quantitative reverse transcription PCR. Both IL-17A and IL-17F mRNA expression levels were significantly lower in blood of patients with mycosis fungoides in comparison with healthy controls. IL-22 serum levels and expression levels of IL-22 mRNA in skin tissue, were significantly increased in patients with mycosis fungoides in comparison with healthy controls. These results suggest that low levels of IL-17A and IL-17F in mycosis fungoides may be connected to impaired immune surveillance contributing to tumourigenesis. Upregulation of IL-22 may play a role in the establishment of the tumour microenvironment in mycosis fungoides.